Correlation of central corneal thickness measurements using Topcon TRK‐1P, Zeiss Visante AS‐OCT and DGH Pachmate 55 handheld ultrasonic pachymeter. (22nd January 2013) - Wells, Matthew; Wu, Nerida; Kokkinakis, Jim; Sutton, Gerard
Abstract : Background: Corneal pachymetry is an important aspect of modern eye care. This study aims to compare the measurement of central corneal thickness (CCT) using automated optical pachymetry, anterior segment optical coherence tomography (AS‐OCT) and ultrasound. Methods: Fifty volunteers participated in this study. Central corneal thickness was measured using the Topcon TRK‐1P (Topcon, Tokyo, Japan) automated optical pachymeter, the Visante AS‐OCT (Carl Ziess Meditec, Dublin, CA, USA) and the Pachmate 55 handheld ultrasonic pachymeter (DGH, Exton, PA, USA). Pearson correlation coefficients were calculated to compare automated optical pachymetry and AS‐OCT with ultrasound. Bland–Altman plots were generated and limits of agreement (LOA) calculated. Results: Fifty eyes were measured for comparison. The mean and standard deviation of the CCT measured by optical pachymetry was 523.7 ± 42.3 μm (range: 412 to 594), 536.0 ± 36.9 μm (range: 425 to 607) for AS‐OCT and 553.4 ± 40.7 μm (range: 431 to 630) for ultrasound. Comparison of optical pachymetry and AS‐OCT with ultrasound, generated Pearson correlation coefficients of 0.96 and 0.98, respectively. Measurements using optical pachymetry and AS‐OCT were consistently lower than when measuring with ultrasound. Bland–Altman plots revealed mean differences of 29.7 μm between optical pachymetry and ultrasound (LOA ‐5.4 to ‐54.1) and of 17.4 μm (LOA +0.9 to ‐35.7) between AS‐OCT and ultrasound. Conclusion: Due to AS‐OCT and automated optical pachymetry consistently measuring lower than ultrasound, it should be noted that these devices are not interchangeable in clinical practice.